La dinámica metropolitana en España. Análisis estadístico y cartográfico de los municipios a partir de la población y la vivienda - De Cos Guerra, O. (Geographicalia, 2015)
The analysis of demographic dynamic on municipal scale in Spain shows the existence of organized aureoles around the main urban municipalities. Likewise, the selection of significant sociodemographic variables lets to stand out relatively homogeneous behaviors in the areas of influence of the main urban systems. These aspects are the ones that since a statistical and cartographic perspective are incorporated in the present study. It is based on the base of the importance of the new promotions in the internal processes of redistribution.